1986
DOI: 10.1159/000138152
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Proteinuria in Diabetes mellitus by Sorbinil, an Aldose Reductase Inhibitor

Abstract: Proteinuria was diminished by concomitant oral administration of sorbinil, an aldose reductase inhibitor to streptozotocin-induced diabetic rats. Animals were placed in one of three groups: control, diabetic, sorbinil-treated diabetic. For a period of 10 weeks, 24-hour urine samples were analyzed weekly for volume, glucose, ketone, total protein (Pesce-Strande) and individual protein components having molecular weights between 15,000 and 120,000 daltons. The latter were examined by polyacrylamide gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 10 publications
1
24
1
Order By: Relevance
“…Mean_+ SEM are shown. There were six rats in each group UAE/GFR GFR/kg body Bg/ml.min ~ mass ml-min-l/kg This study has confirmed that inhibition of the enzyme aldose reductase by two structurally unrelated compounds partially prevents the increase in UAE observed in rats with diabetes induced by STZ [15,17,21,22]. It has also confirmed the findings of Craven et al [22] that the enhanced PG production by glomeruli isolated from STZ diabetic rats is reduced by treatment with ARI.…”
Section: Glornerular Sorbitol Content In Non-diabetic Rats and Rats Asupporting
confidence: 67%
See 1 more Smart Citation
“…Mean_+ SEM are shown. There were six rats in each group UAE/GFR GFR/kg body Bg/ml.min ~ mass ml-min-l/kg This study has confirmed that inhibition of the enzyme aldose reductase by two structurally unrelated compounds partially prevents the increase in UAE observed in rats with diabetes induced by STZ [15,17,21,22]. It has also confirmed the findings of Craven et al [22] that the enhanced PG production by glomeruli isolated from STZ diabetic rats is reduced by treatment with ARI.…”
Section: Glornerular Sorbitol Content In Non-diabetic Rats and Rats Asupporting
confidence: 67%
“…These include increased glomerular filtration rate (GFR) [1][2][3][4][5][6][7][8][9][10][11][12][13], increased urinary albumin excretion (UAE) [13][14][15][16][17], increased production of vasoactive prostaglandins (PGs) by renal glomeruli [10,[18][19][20], and increased glomerular sorbitol accumulation [21]. Although there are several plausible ways in which these changes could be related, the data linking these phenomena have been conflicting and confusing.…”
mentioning
confidence: 99%
“…Previously, we reported that the aldose reductase inhibi tor (ARI), sorbinil, prevented and/or reversed proteinuria as determined by analysis of total urinary' protein excretion and the array of individual urinary proteins for a period of 4 months [3][4][5], In the present study, the objec tives were 2-fold. First, the sorbinil study was extended to 6 months.…”
Section: Introductionmentioning
confidence: 62%
“…This is deducted from short-term studies in streptozotocin diabetic (SZT-D) (IDDM) animals showing that early administration of aldose reductase inhibitors reduces the increased GFR [5,6] and partly reduces the increased urinary albumin excretion [6][7][8]24]. The results of the studies on the effect of dietary myo -inositol sUpplementation on the GFR differ.…”
Section: Discussionmentioning
confidence: 99%